Stan badań nad środowiskiem literackim Gorzowa Wielkopolskiego i okolic - rekonesans i perspektywy rozwojowe = Research on the literary environment of Gorzow Wielkopolski and its surroundings: current insights and future prospects - Turska, Magdalena (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article aims to assess the extent of research conducted on the literary heritage of Gorzow Wielkopolski and its surrounding regions. The study involves an examination of the available literature in the Regional Collection Department of the Zbigniew Herbert Regional and Municipal Public Library in Gorzow Wielkopolski, supplemented by a bibliographic query of the catalogues of the National Library of Poland.
Keywords: literatura regionalna; środowisko literackie Gorzowa Wielkopolskiego; badania literaturoznawcze; kwerenda; regional literature; literary environment of Gorzow Wielkopolski; literary studies; bibliographic query